2022
DOI: 10.1186/s13059-022-02800-0
|View full text |Cite
|
Sign up to set email alerts
|

New roles for AP-1/JUNB in cell cycle control and tumorigenic cell invasion via regulation of cyclin E1 and TGF-β2

Abstract: Background JUNB transcription factor contributes to the formation of the ubiquitous transcriptional complex AP-1 involved in the control of many physiological and disease-associated functions. The roles of JUNB in the control of cell division and tumorigenic processes are acknowledged but still unclear. Results Here, we report the results of combined transcriptomic, genomic, and functional studies showing that JUNB promotes cell cycle progression v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 79 publications
2
11
0
Order By: Relevance
“…Further evidence suggests that ZNF331 can act upstream, including the presence of ChIP-seq peaks at both 5’ and 3’ of JUNB (Figure 6d). ZNF331 OE also induces G2 cell cycle arrest in cancer 39 ; assuming JUNB is related to cell cycle control, as suggested by our cluster, and previously shown 40 , then the phenotype of ZNF331 OE is also consistent with being upstream. However, we expect the regulation of JUNB to be more complex than being run by a single gene.…”
Section: Introductionsupporting
confidence: 80%
“…Further evidence suggests that ZNF331 can act upstream, including the presence of ChIP-seq peaks at both 5’ and 3’ of JUNB (Figure 6d). ZNF331 OE also induces G2 cell cycle arrest in cancer 39 ; assuming JUNB is related to cell cycle control, as suggested by our cluster, and previously shown 40 , then the phenotype of ZNF331 OE is also consistent with being upstream. However, we expect the regulation of JUNB to be more complex than being run by a single gene.…”
Section: Introductionsupporting
confidence: 80%
“…These vasculature genes included Efnb2 , a member of the ephrin family and a pro-angiogenic factor whose overexpression predicts the poor prognosis of solid tumors [ 43 , 44 , 45 ], and Id1 , a helix–loop–helix transcription factor that regulates tumor angiogenesis [ 46 ] ( Figure 4 E,F). BaP upregulated the expression levels of these pro-angiogenic and pro-tumorigenic factors [ 47 , 48 , 49 ] in male MRL lungs more than in their female counterparts ( Figure 4 F). Immunofluorescence staining also showed that there was an increase in the number of EFNB2-positve cells in the lungs of BaP-treated MRL mice, an effect more substantial in males than females ( Figure 4 G,H).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we did not examine whether other AP-1 members showed expression correlation with CCL28 and KRAS, or whether they regulated tumour growth. However, previous reports have shown that FOS transcription can mediate YAP/TAZ to promote cell proliferation [ 63 ], JUNB can promote cell cycle progression by inducing cyclin E1 and repressing transforming growth factor (TGF)-β2 genes [ 64 ], and CRTC1 can associate with c-Jun and c-Fos to activate transcription and promote cellular proliferation [ 65 ]. To date, no studies have explored the association between other AP-1 families and CCL28.…”
Section: Discussionmentioning
confidence: 99%